RETRACTED ARTICLE: Long noncoding RNA MAGI1-IT1 promoted invasion and metastasis of epithelial ovarian cancer via the miR-200a/ZEB axis. Issue 12 (18th June 2019) - Gao, Hao; Li, Xiaofeng; Zhan, Guangxi; Zhu, Yong; Yu, Jing; Wang, Jiapo; Li, Li; Wu, Weimin; Liu, Na; Guo, Xiaoqing
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Hao Gao, Xiaofeng Li, Guangxi Zhan, Yong Zhu, Jing Yu, Jiapo Wang, Li Li, Weimin Wu, Na Liu and Xiaoqing Guo. Long noncoding RNA MAGI1-IT1 promoted invasion and metastasis of epithelial ovarian cancer via the miR-200a/ZEB axis. Cell Cycle. 2019;18(12):1393-1406. doi: 10.1080/15384101.2019.1618121 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to fully address the concerns raised and have not been able to provide their original data in the appropriate format. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.